Towards a Micro-Circular Economy in Poultry Production: Integrating Probiotic Substitution and Waste Valorization to Mitigate Environmental Impact - Bodhi Agustono; Maya Nurwartanti Yunita; Zhaza Afililla; Ragil Angga Prastiya; Suciyono; Faizal Ulhaq; Mirza Atikah Madarina Hisyam; Widya Paramita Lokapirnasari (Universitas Airlangga, 2026)
The intensification of the global poultry sector is currently challenged by the need to balance productivity with the mitigation of antimicrobial resistance (AMR) and environmental pollution. This study addresses the technological gap among smallholder farmers in Banyuwangi, Indonesia, by implementing a comprehensive technology transfer program focused on the functional substitution of antibiotic growth promoters (AGPs) with probiotics and the development of waste management cycles. Employing a Participatory Action Research (PAR) framework, the intervention integrated cognitive coaching, technical demonstrations, and longitudinal field applications to bridge the divide between biotechnological innovation and grassroots practice. Data were obtained from 27 broiler farmers through pre- and post-test evaluations and Focus Group Discussions (FGDs) to measure literacy shifts and technical adoption. Quantitative analysis revealed a significant transformation in biotechnology literacy, with understanding of probiotic mechanisms increasing from 37.0% (baseline) to 85.2% post-intervention. Furthermore, technical competence in functional feed formulation improved by 33.4% (p < 0.05), while the intention to adopt sustainable practices increased to 96.3%. These findings indicate that barriers to adoption among smallholders are primarily driven by limited access to applied science rather than cultural resistance. The study concludes that this hybrid extension model successfully establishes a viable micro-circular economy, offering a replicable strategy for upstream AMR mitigation in developing agropolitan regions.